Modal Substitution in Koine Greek: the Gospels of Mark and Luke - Redondo, Jordi (Scripta classica israelica, 2018)
This paper continues our former research on the Greek Koine from a diachronic perspective. Our main goal deals with the use of the subjunctive and optative moods both in main and in subordinate clauses. The direct corpus of our analysis consists of the Gospels of Luke and Mark, as they represent a more literary (Luke) and a rather non-literary Greek Koine (Mark). Other contemporary texts, including non-literary evidences, are also used as a reference in order to establish the extent of some tendencies. The results obtained contribute to the understanding of the decline of the subjunctive and optative moods.